Digital signal processing a computer-based approach - Mitra, Sanjit Kumar (McGraw-Hill series in electrical engineering. Communications and signal processing, 1998)
This text introduces the tools for the analysis and design of discrete-time systems. Starting with a review of fundamental theory, it includes methods for the design of linear time-invariant discrete-time systems to meet prescribed design specifications.